Forest, Trees, Dynamics: Results from a Novel Wisconsin Card Sorting Test Variant Protocol for Studying Global-Local Attention and Complex Cognitive Processes - Cowley, Benjamin; Lukander, Kristian (Frontiers in Psychology, 2016)
Background Recognition of objects and their context relies heavily on the integrated functioning of global and local visual processing. In a realistic setting such as work, this processing becomes a sustained activity, implying a consequent interaction with executive functions. Motivation There have been many studies of either global-local attention or executive functions; however it is relatively novel to combine these processes to study a more ecological form of attention. We aim to explore the phenomenon of global-local processing during a task requiring sustained attention and working memory. Methods We develop and test a novel protocol for global-local dissociation, with task structure including phases of divided ('rule search') and selective ('rule found') attention, based on the Wisconsin Card Sorting Task. We test it in a laboratory study with 25 participants, and report on behaviour measures (physiological data was also gathered, but not reported here). We develop novel stimuli with more naturalistic levels of information and noise, based primarily on face photographs, with consequently more ecological validity. Results We report behavioural results indicating that sustained difficulty when participants test their hypotheses impacts matching-task performance, and diminishes the global precedence effect. Results also show a dissociation between subjectively experienced difficulty and objective dimension of performance, and establish the internal validity of the protocol. Contribution We contribute an advance in the state of the art for testing global-local attention processes in concert with complex cognition. With three results we establish a connection between global-local dissociation and aspects of complex cognition. Our protocol also improves ecological validity and opens options for testing additional interactions in future work.